(untitled) (Journal of the College of Basic Education, 2022)
It can be said that there is no literary epoch that has exposed researchers to injustice, injustice and ambiguity like the Ottoman era. It was described as decadence and regression at times, and at other times the "dark period". Some of them introduced the term (successive states) (1) as a reservation. What prompted them to take such epithets is their opinion of the Ottoman era, in which - according to their saying - the faculty of the tongue was corrupted and the senses froze, and poetry was afflicted with what afflicted all the Arab literatures of this era of weakness and decline, when it took hold of stagnation over the signs, and the nation was humiliated in that period. the dark period, and the writer or poet became interested in embellishing phrases with alliteration, puns, and assonance” (2